The truth of myth : world mythology in theory and everyday life - Thompson, Tok; Schrempp, Gregory (New York : Oxford universty press, 2020)
To the student of myth: This book attempts to provide a concise overview of the theoretical approaches to studying mythology, both in theory and in everyday life. Whether one is interested in a particular myth or mythic tradition, or understanding comparative mythology more broadly, or even the subject and overview of mythology as a whole, this text attempts to present a clear and understandable introduction to some of the best tried and true approaches, as well as to address some of the perennial problems and points of confusion.
Prologue Introduction Chapter 1: Definitions and Starting Points Chapter 2: Highlights in the History of Mythological Research Chapter 3: Studying Mythology Comparatively Chapter 4: Some Current Trends Conclusion Glossary Works Cited Index.
Includes bibliographical references and index.
Keywords: Cultural Characteristics; Manners and customs; Mythology